A SYSTEM DYNAMICS APPROACH TO MODEL REHABILITATION OF IRRIGATION NETWORKS CASE STUDY: QAZVIN IRRIGATION NETWORK, IRAN1. (22nd March 2013) - Vaez Tehrani, Mahsa; Monem, Mohammad Javad; Bagheri, Ali
ABSTRACT: Assessment of irrigation networks shows that their utility is less than what is expected because of poor performance. Poor performance of irrigation networks is partly due to their aged condition, which requires rehabilitation. Rehabilitation of irrigation systems is commonly practised on a basis lacking integration; thus they have not led to considerable improvement. Integration requires a systemic approach and system dynamics methodology provides a practical tool to implement integration in a complex system such as an irrigation system. Using system dynamics modelling, the paper intends to evaluate several rehabilitation policies in the Qazvin Irrigation Network, in mid‐northern Iran, and then the effects of policies on performance elements (efficiency) will be investigated. The main elements that affect network utility are considered to be efficiency, adequacy, equity, flexibility and stability in water delivery. Three policies for network rehabilitation are considered to be: fixing the crop area, decreasing drawdown of groundwater, and increasing investment in renovation projects. The results show that all of these three policies improve system utility; however, the 'fixing the crop area' policy showed a better improvement. Copyright © 2013 John Wiley & Sons, Ltd.